Greater Vulnerability of the Infecting Viral Strand of Replicative-Form Deoxyribonucleic Acid of Bacteriophage φX174 - Datta, B. (1970)
Four types of φX-infected cells of Escherichia coli CR, a thymine-requiring strain of E. coli C, were prepared in which the parental replicative-form deoxyribonucleic acid (RF DNA) was labeled with same specific amounts of bromouracil in (i) both strands, (ii) only the infecting viral strand, (iii) only the complementary strand, and (iv) neither strand. The sensitivity of each type of infected cell toward irradiation by ultraviolet light, visible light, and X rays was measured. The results indicate that a certain amount of radiation damage in the infecting viral strand of the parental RF was more inhibitory to the production of progeny phage than when the damage was in the complementary strand. Similar conclusions were also drawn from “suicide” experiments of the phage-infected complexes containing (32)P of the same specific activity on either strand of the parental RF DNA. The results suggest that the beta decay occurring in the infecting viral strand was more effective in inactivating the plaque-forming ability of the complex.